1995
DOI: 10.1111/j.1469-1809.1995.tb01603.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of VAV2 on 9q34 and its exclusion as the tuberous sclerosis gene TSC1

Abstract: A novel widely expressed homologue of the VAV oncogene, VAV2 (53% identical residues), has been identified within the critical region for the tuberous sclerosis gene, TSC1, on human chromosome 9q34. By Southern blot analysis, analysis of allele-specific transcription, and direct sequencing of the VAV2 mRNA/cDNA from patient lymphoblastoid cell lines, we demonstrate that both alleles of this gene are expressed in TSC patients and there are no significant mutations. VAV consists of a novel array of signalling do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 45 publications
0
62
0
Order By: Relevance
“…Our results argue that similar roles may be played by Vav2 and CrkL, as well. Tyrosine phosphorylation of Vav2, a ubiquitously expressed form of Vav (Henske et al, 1995), known to activate Rho-like GTPases in a tyrosine phosphorylationdependent manner (Schuebel et al, 1998), is increased in both wild-type c-Cbl-and Tyr 5 -4Phe-overexpressing v-Abl-transformed NIH3T3 cells, as compared to vector control cells (data not shown). However, only wild-type c-Cbl is co-immunoprecipitated with Vav2 (data not shown), consistent with the previously shown role of tyrosine-700 of c-Cbl as the Vav-binding site for this protein (Marengere et al, 1997).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our results argue that similar roles may be played by Vav2 and CrkL, as well. Tyrosine phosphorylation of Vav2, a ubiquitously expressed form of Vav (Henske et al, 1995), known to activate Rho-like GTPases in a tyrosine phosphorylationdependent manner (Schuebel et al, 1998), is increased in both wild-type c-Cbl-and Tyr 5 -4Phe-overexpressing v-Abl-transformed NIH3T3 cells, as compared to vector control cells (data not shown). However, only wild-type c-Cbl is co-immunoprecipitated with Vav2 (data not shown), consistent with the previously shown role of tyrosine-700 of c-Cbl as the Vav-binding site for this protein (Marengere et al, 1997).…”
Section: Discussionmentioning
confidence: 91%
“…The analysis of morphology of transfected cells showed that expression of dominant-inhibitory p85 reduced their spreading on FN, while expression of wild-type p85 facilitated their spreading on FN as compared to the corresponding vector-transfected cells (Figure 8b). The Considering the importance of Vav GEFs for the activation of Rho-like GTPases, we also analysed tyrosine phosphorylation of Vav2, a ubiquitously expressed form of Vav (Henske et al, 1995), in control, c-Cbl-and Tyr 5 -4Phe-overexpressing v-Abl-transformed NIH3T3 cells. Tyrosine phosphorylation of Vav2 was increased both in cells expressing wild-type cCbl and in those expressing Tyr 5 -4Phe, as compared to vector control cells (data not shown).…”
Section: Role Of Rho-family Gtpases In C-cbl-induced Effects In V-ablmentioning
confidence: 99%
“…Sequence alignment of vavSH3C with other SH3 domains revealed that it is almost identical (98%) to the SH3 domain of vav2, another member of the vav family of proteins (Henske et al, 1995). As there is yet no structural or functional information relating to the SH3 domain of vav2, we searched for additional SH3 domains that resemble that of Vav.…”
Section: Transforming Potential Of Mutant Vav Sh3c Proteinsmentioning
confidence: 99%
“…The 3 mammalian Vav proteins (Vav1, Vav2, and Vav3) differ in their tissue distribution. Vav1 is primarily expressed in hematopoietic cells, whereas Vav2 and Vav3 are more ubiquitously expressed (12)(13)(14). Vav proteins contain multiple function motifs and are involved in various cellular signaling processes, including cytoskeleton organization, cell transformation, and oncogenesis (15,16).…”
Section: Introductionmentioning
confidence: 99%